Breaking Barriers to Global Education: Investigating the Experiences of Middle-Income Students in Study Abroad Programs - Hidayati, Inayah (Global and Policy Journal of International Relations, 2023)
Everyone has the right to a complete education, yet certain demographic groups face barriers. Study abroad programs help students understand global issues and improve their academic and career skills. International education migration can be tough for middle-class people. This study examines how educational quality and study-abroad programs affect international migration. This study examines how study abroad affects student academic and professional success. Middle-income students may need more study-abroad opportunities. Interviews are used in qualitative research on study abroad students. This project aims to improve study-abroad programs for students from different socioeconomic origins, emphasising disadvantaged groups. According to studies, economically disadvantaged students may confront many problems when studying abroad. They include financial, cultural, and linguistic barriers and social isolation. Scholarships and financial aid also promote justice and increase study-abroad access. The above funds can help economically disadvantaged students pay for study abroad programs by reducing travel, tuition, and living expenses. The widespread distribution of scholarship program information and its accessibility can help all youngsters receive a comprehensive education and accomplish their academic and occupational goals. This research could help build Sustainable Development Goal 4 policy and implementation techniques. It promotes and improves high-quality education. Furthermore, these discoveries can improve global educational parity.DOI: https://doi.org/10.33005/jgp.v11i02.4140